2021
DOI: 10.1002/ange.202112183
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Strain Phosphate Cathode for High‐Rate and Ultralong Cycle‐Life Potassium‐Ion Batteries

Abstract: Most potassium-ion battery (PIB) cathode materials have deficient structural stability because of the huge radius of potassium ion, leading to inferior cycling performance.W e report the controllable synthesis of an ovel low-strain phosphate material K 3 (VO)(HV 2 O 3 )(PO 4 ) 2 (HPO 4 )(denoted KVP) nanorulers as an efficient cathode for PIBs.The as-synthesized KVP nanoruler cathode exhibits an initial reversible capacity of 80.6 mAh g À1 under 20 mA g À1 ,with alarge average working potential of 4.11 V. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…[10][11][12][13][14] However, the practical application of potassium-ion batteries is restricted due to the larger ion radius of K + , which leads to poor kinetics and terrible cycle life. [15][16][17][18] Therefore, it is significant and urgent to design high-performance electrode materials with high conductivity and structural stability to promote the development of potassium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] However, the practical application of potassium-ion batteries is restricted due to the larger ion radius of K + , which leads to poor kinetics and terrible cycle life. [15][16][17][18] Therefore, it is significant and urgent to design high-performance electrode materials with high conductivity and structural stability to promote the development of potassium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…6 showcases the average voltages achieved by various polyanion-based cathode compounds reported thus far for KIBs. Vanadiumbased orthophosphates (e.g., K 3 V 3 (PO 4 ) 4 , 168 K 3 V 3 (PO 4 ) 4 H 2 O, 169 K 3 V 2 (PO 4 ) 3 162,170 ), fluorophosphates (KV 0.5 Ti 0.5 PO 4 F, 171 KVPO 4 F, 18,159 174 oxyphosphates (KVOPO 4 ), 18,175 and pyrophosphates (KVP 2 O 7 ) 176,177 exhibit high voltages, reaching 4 V and even beyond, whilst maintaining fast rate capabilities and good cyclability. Mixed polyanion compounds, such as K 6 (VO) 2 (V 2 O 3 ) 2 (PO 4 ) 4 -(P 2 O 7 ), 178,179 also exhibit high voltages surpassing 4 V. Titanium-based fluorophosphates like KTiPO 4 F exhibit voltages of 3.6-3.7 V (Fig.…”
Section: Polyanion-based Compoundsmentioning
confidence: 99%
“…Vanadium-based orthophosphates ( e.g. , K 3 V 3 (PO 4 ) 4 , 168 K 3 V 3 (PO 4 ) 4 H 2 O, 169 K 3 V 2 (PO 4 ) 3 162,170 ), fluorophosphates (KV 0.5 Ti 0.5 PO 4 F, 171 KVPO 4 F, 18,159 K 1.5 VOPO 4 F 0.5 , 172 K 3 V 2 O 2 (PO 4 ) 2 F, 163 KVPO 4 F 0.5 O 0.5 173 ), K 3 (VO)(HV 2 O 3 )(PO 4 ) 2 (HPO 4 ), 174 oxyphosphates (KVOPO 4 ), 18,175 and pyrophosphates (KVP 2 O 7 ) 176,177 exhibit high voltages, reaching 4 V and even beyond, whilst maintaining fast rate capabilities and good cyclability. Mixed polyanion compounds, such as K 6 (VO) 2 (V 2 O 3 ) 2 (PO 4 ) 4 (P 2 O 7 ), 178,179 also exhibit high voltages surpassing 4 V.…”
Section: High Performance Cathode Materialsmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) with high energy density are currently the leading technology for electrochemical energy storage, but the rareness, ununiform distribution, and fast consumption of Li resources have caused concern about their sustainability and cost. , New rechargeable battery systems based on abundant resources are being intensively explored. In this regard, K-ion batteries (KIBs) are drawing increasing research interest due to the high natural abundance of K resources in the earth’s crust (1.5 wt %, in contrast to 0.0017 wt % for Li) and the lower K + /K potential. Especially, it is identified that the K + /K potential could be even lower than that of both Li + /Li and Na + /Na in a common electrolyte of KPF 6 in EC/DEC, which promised significant potential for building high-voltage KIBs .…”
Section: Introductionmentioning
confidence: 99%